An Introduction To Green Marketing-Emerging Dimensions, Strategies, Opportunities, Challenges and Trends: A Review - Jyoti, Jiwan (Journal of Management and Science, 2013)
Green marketing is a phenomenon which has developed particular important in the modern market. This concept has enabled for the re-marketing and packaging of existing products which already adhere to such guidelines. The importance of Green Marketing can well be emphasised by stating the fact that majority of consumers in all the countries want to buy from environmentally responsible companies. Consumers say environmental consciousness is an important corporate priority – ranking behind good value, trustworthy, and cares about customers. Consumers expect green companies to engage in a broad set of actions, particularly reducing toxics, recycling and managing water. Many consumers prefer to spend more on green products, especially in developing economies. Green marketing is a phenomenon which has developed particular important in the modern market. This concept has enabled for the remarketing and packaging of existing products which already adhere to such guidelines.Additionally, the development of green marketing has opened the door of opportunity for companies to co-brand their products into separate line, lauding the green-friendliness of some while ignoring that of others. Such marketing techniques will be explained as a direct result of movement in the minds of the consumer market. As a result of this businesses have increased their rate of targeting consumers who are concerned about the environment.